Synthesis of an Ag3PO4/Nb2O5 photocatalyst for the degradation of dye - Osman, Nur Syazwani; Sulaiman, Siti Norhasimah; Muhamad, Ernee Noryana; Mukhair, Hayati; Sin, Tee Tan; Abdullah, Abdul Halim (MDPI AG, 2021)
In this work, the photocatalytic performance of Ag3PO4, Nb2O5 and Ag3PO4/Nb2O5 hybrid photocatalysts to degrade methyl orange dye, MO, in an aqueous solution under visible light irradiation was evaluated. The Ag3PO4 and Ag3PO4/Nb2O5 photocatalysts, with various Ag to Nb molar ratios, were prepared using a facile precipitation method. The photocatalysts were characterized by X-ray diffraction, UV–Visible, X-ray Photoelectron, and Photoluminescence spectroscopies. Upon the addition of Ag3PO4, the band gap energy of Nb2O5 decreased from 3.0 eV to 2.7 eV, indicating the possible use of the Ag3PO4/Nb2O5 hybrid photocatalysts under visible light irradiation. All of the prepared Ag3PO4/Nb2O5 catalysts exhibited higher photocatalytic performance than Ag3PO4 in degrading methyl orange dye under 23-watt visible light irradiation. The Ag3PO4/Nb2O5 catalyst, with a mole ratio of 2:1, exhibited the fastest MO degradation rate of 7.3 × 10−2 min−1, which is twice faster than that of Ag3PO4. The catalyst also shows better stability, as it is reusable for up to six experimental cycles while maintaining its photocatalytic activity above 60%.